Thermal Conductivity of Nanofluid, a Mini Review - Ayad Dari Jaafar; Dhiyaa A. Hussein Al-Timimi; Mohammed Jaafar Ali Alatabe; Mohammed Shorbaz; Ban kadhim Abed (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The rapid development of the world and the increasing need to increase the efficiency of devices in many applications has led to the development of fluid conductivity with more efficient heat transfer has made it necessary to enhance heat transfer to meet the cooling challenge, as is the case in the photonics, electronics, power supply and transportation industries. Nanofluids and methods for measuring them have been developed and studied to facilitate the interpretation of their behavior, including thermal behavior. The study aimed to gain a fundamental and experimental understanding of the thermal behavior of nanofluids by examining thermal conductivity, preparation techniques, stability-enhancing agents, and measurement techniques. With changes in shape, concentration, and temperature, nanofluids exhibit significantly improved thermal conductivity. In addition, efforts have been made to introduce new and accurate correlations for estimating thermal conductivity at different concentrations and temperatures.